PENGARUH MINAT BELAJAR TERHADAP HASIL BELAJAR SISWA MATA PELAJARAN IPS TERPADU DI SMPN 2 - Kusnawati, Eti; ., Sulistyarini; ., Aminuyati (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2014)
Abstract: Abstract: This thesis entitled influence students' interest towards learning outcome of students in social studies Integrated SMP Negeri 2 Tanah Pinoh Melawi District school year 2013-2014. Thisis the research problem (1) How can student interest grade VIII SMP Negeri 2 Tanah Pinoh Melawi District? (2) How do the results of student learning in social studies Integrated class VIII SMP Negeri 2 Tanah Pinoh Melawi District 2? (3) Is there any influence between students' interest towards learning outcome of students in social studies Integrated classes VIII SMP Negeri 2 Tanah Pinoh District Melwi ?. The method used is descriptive method in the form of association studies (Interrelationship Studies). The sample was students of SMP Negeri 2 as many as 42 students. The results showed that there are significant between the independent variable (X) on the dependent variable (Y) which is shown in the equation Y = 44,587 + 0,226X and test hypothesis test t count> t table or 4,499> 2,021. The magnitude of the effect of the coefficient of determination of test results with SPSS 16 is equal to 7,1% while 29% is influenced by other factors. Keywords: Interest in learning, learning outcomes, Integrated Social Studies Abstrak: Skripsi ini berjudul pengaruh minat belajar siswa terhadap hasil belajar siswa pada mata pelajaran IPS Terpadu kelas VIII SMP Negeri 2 Tanah Pinoh Kabupaten Melawi Tahun ajaran 2013-2014. Masalah penelitian iniadalah (1) Bagaimanakah minat belajar siswa kelas VIII SMP Negeri 2 Tanah Pinoh Kabupaten Melawi? (2) Bagaimanakah hasil belajar siswa pada mata pelajaran IPS Terpadu kelas VIII SMP Negeri 2 Tanah Pinoh Kabupaten Melawi? (3) Apakah terdapat pengaruh antara minat belajar siswa terhadap hasil belajar siswa pada mata pelajaran IPS Terpadu kelas VIII SMP Negeri 2 Tanah Pinoh Kabupaten Melwi?. Metode yang digunakan adalah metode deskriftif dalam bentuk studi hubungan (Interrelationship Studies). Sampel penelitian ini adalah siswa SMP Negeri 2 sebanyak 42 siswa. Hasil penelitian menunjukkan bahwa terdapat pengaruh antara variabel bebas (X) terhadap variabel terikat (Y) yang mana ditunjukkan dalam persamaan Y = 44,587+0,226X dan uji hipotesis uji t hitung > t tabel atau 4.499 > 2,021. Adapun besarnya pengaruh dari Hasil uji koefisien determinasi dengan SPSS 16 adalah sebesar 71% sedangkan 29% sisanya dipengaruhi oleh faktor-faktor lain. Kata Kunci : Minat belajar, Hasil belajar, Pelajaran IPS Terpadu